Respostas

  • Usuário do Brainly
2014-07-21T18:18:22-03:00
A)

(- \frac{1}{2} ) ^{2} .( \frac{3}{2} )-( \frac{2}{3}) ^{3}  :(- \frac{1}{27} )=

 \frac{1}{4} .( \frac{3}{2} )-( \frac{8}{27}).(- \frac{27}{1}  =

 \frac{3}{8} -(-8)=

 \frac{3}{8} +8= \frac{3+64}{8} = \frac{67}{8}

b)
( \frac{1}{10} ) ^{2} :(-2)+( \frac{15}{10} ).(- \frac{1}{10} ) ^{2} =

 \frac{1}{100}.(- \frac{1}{2} ) +( \frac{15}{10}) .(\frac{1}{100} )=

simplifica 15 com 10

- \frac{1}{200} +( \frac{3}{2} ). (\frac{1}{100} )=

- \frac{1}{200} + \frac{3}{200} = \frac{2}{200} = \frac{1}{100} =0,01

4)
a)
4-2x=x+31

-3x=27

3x=-27

x=- \frac{27}{3}

x=-9

S={-9}

b)
5-2(y-1)=y+4(-2+3y)

5-2y+2=y-8+12

-15y=-15

15y=15

y=1

S={1}